The effect of core stability training on dynamic balance and smash stroke performance in badminton players - An evidence based study - Solanki, H. G.; Gill, M. A. (International Journal of Science and Healthcare Research, 2021)
Background: Badminton is one of the most popular sports and fastest racket sports in the world in which single or double players striking shuttle cock to and fro across the net to score a point. The important components for badminton players are muscle strength, muscular endurance, power, speed, agility, flexibility, balance and coordination. Core stability training is one of the essential fitness components of any racket sports player, especially for badminton players during smashing the shuttlecock smash through the game. Purpose: The purpose is to study the scientific evidences regarding the effect of core stability training on dynamic balance and smash stroke performance in badminton players. Methodology: A search for relevant articles was carried out using key words- Badminton, core stability training, dynamic balance and smash stroke performance and search engines- Google Scholar, PubMed, PEDro, Science Direct, SPOERT Discuss, Research Gate and CINAHL. Studies were selected from year 2010-2019. Ten studies were included in which there were 2 systemic reviews, 5 RCT, 2 correlation study, 2 experimental study, and 1 cross sectional study. Results: 12 studies were reviewed from which 11 studies concluded that core stability training is effective in improving dynamic balance and smash stroke performance in badminton players. Conclusion: Based on the analysis of these 12 articles, it can be concluded that core stability training is effective in improving dynamic balance and smash stroke performance in badminton players. Clinical Implication: Core stability training is found to be effective improving and smash stroke performance in athletes with various racquet sports and can be performed to improve athletics skill performance.